2022
DOI: 10.1002/ueg2.12344
|View full text |Cite
|
Sign up to set email alerts
|

Post‐pancreatitis diabetes mellitus is common in chronic pancreatitis and is associated with adverse outcomes

Abstract: Background: Post-pancreatitis diabetes mellitus (PPDM) is a common consequence of chronic pancreatitis (CP). We aimed to determine the incidence and predictors of PPDM after CP onset, as well as complications and antidiabetic therapy requirements, in a high-volume tertiary center. Methods:We did a cohort study with retrospectively collected data from patients with definite CP seen at the Karolinska University Hospital between January 1999 and December 2020. Cause-specific Cox regression analysis was used to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“… 11 Moreover, compared to comorbidity in CP‐T2D, patients with diabetes related to CP present a more aggressive phenotype (microangiopathy and infection) and higher need for glucose‐lowering treatment, and even patients who experience their first attack of pancreatitis may require long‐term management after being discharged from the hospital. 12 , 13 Taken together, CP and T2D exhibit a strong correlation during the progression of the disease. However, the shared signatures and underlying pathogenesis of comorbidity are still not fully understood.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“… 11 Moreover, compared to comorbidity in CP‐T2D, patients with diabetes related to CP present a more aggressive phenotype (microangiopathy and infection) and higher need for glucose‐lowering treatment, and even patients who experience their first attack of pancreatitis may require long‐term management after being discharged from the hospital. 12 , 13 Taken together, CP and T2D exhibit a strong correlation during the progression of the disease. However, the shared signatures and underlying pathogenesis of comorbidity are still not fully understood.…”
Section: Introductionmentioning
confidence: 90%
“…Another study showed that the combination of CP and T2D can lead to a mutually aggravating process involving insulin resistance, chronic low‐intensity inflammation, and dyslipidemia 11 . Moreover, compared to comorbidity in CP‐T2D, patients with diabetes related to CP present a more aggressive phenotype (microangiopathy and infection) and higher need for glucose‐lowering treatment, and even patients who experience their first attack of pancreatitis may require long‐term management after being discharged from the hospital 12,13 . Taken together, CP and T2D exhibit a strong correlation during the progression of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion and exclusion criteria for PPDM-A group were as follows: inclusion criteria: (I) patients were diagnosed with diabetes mellitus >90 days after the date of first pancreatitis diagnosis ( 24 , 25 , 28 ); (II) upper abdominal CECT examinations performed within 7 days of the onset of AP; and (III) inpatients. Exclusion criteria: (I) having any history of diabetes; (II) elevated blood glucose during hospitalization; (III) high blood glucose within 90 days after discharge; (IV) acute onset of chronic pancreatitis; (V) cancer or severe chronic wasting diseases; (VI) loss to follow-up; (VII) unsatisfactory images or incomplete medical records; and (VIII) less than 18 years of age.…”
Section: Methodsmentioning
confidence: 99%
“…
R
Comments on Post-pancreatitis diabetes mellitus is common in chronic pancreatitis and is associated with adverse outcomesDear Editors, We read with great interest the recently published study on postpancreatitis diabetes mellitus (PPDM) in chronic pancreatitis and its association with adverse outcomes. 1 The authors concluded that patients with PPDM have a higher frequency of clinical complications and are more commonly prescribed insulin and metformin. The study is valuable; however, we identified some points that require further clarification.
…”
mentioning
confidence: 99%